Respons Peserta Didik dalam Proses Pembelajaran di Sekolah Dasar Kristen Generasi Unggul, Kota Kupang - Risambessy, Johanis; Sau, Eliazar; Muloko, Vicky; Fanggidae, Yulfiana (SEKOLAH TINGGI TEOLOGI INJILI SETIA SIAU, 2024)
Learners responsses in the learning process of Christian Religious Education need to be measured holistically. This study aims to measure the responses of 39 learners at Sekolah Dasar Kristen Generasi Unggul, Kota Kupang, Kupang City in terms of response and reaction indicators. Data were analyzed quantitatively descriptively. The results showed that the overall learner responsse touched 90.6% and included a very positive category. The confidence sub-indicator received a percentage of 94.2%, followed by the satisfaction (92.1%), interest (89.1%), and relevance (88.5%) sub-indicators. Recommendation, Christian Religious Education teachers can use Microsoft Office PowerPoint learning media because student responsses are positive, seen from their confidence, satisfaction, and interest in the material because it is relevant to everyday life.